1991
DOI: 10.1152/ajpheart.1991.261.4.21
|View full text |Cite
|
Sign up to set email alerts
|

A 90-kDa surface antigen of immature smooth muscle cells is ICAM-1

Abstract: A monoclonal antibody, designated 10F3, that reacts with an antigen of molecular mass 90,000 Da has been developed by immunization of BALB/c mice with smooth muscle cells in long-term culture. The cells were originally isolated from fetal human aorta. The 10F3 was identified as an antibody that reacts with the ICAM-1 molecule. ICAM-1 is a mesenchymal antigen that is lost during differentiation of cells other than endothelium but is reexpressed by the intimal cells of vessels involved in atherogenesis. atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Indeed, knockout mice which are caspase1 deficient and therefore do not generate mature IL‐1β develop normally and the ex vivo response of cells to various apoptotic stimuli is indistinguishable from cells derived from wild‐type animals [12]. In addition, as 7β‐hydroxycholesterol and 7‐ketocholesterol can stimulate IL‐8 production which is chemotactic for T lymphocytes and neutrophils at picomolar and nanomolar concentrations [37], and as IL‐1 can induce both in vitro and in vivo endothelial expression of the adhesion molecules E‐selectin, ICAM‐1 and VCAM‐1 which are involved in the local adhesion and the subendothelial accumulation of T‐cells and monocytes [38, 39], we speculate that these oxysterols could play a critical role in the recruitment of immunocompetent cells in the atherosclerotic plaque. Interestingly, Bcl‐2 overexpression was associated with a lower IL‐1β secretion in U4 cells treated with 7β‐hydroxycholesterol than in U4 cells treated with 7‐ketocholesterol suggesting that the biological effects of oxysterols could be structure dependent as previously supposed by the various potencies of these compounds to induce apoptosis [3, 5]and to inhibit 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase activity [40].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, knockout mice which are caspase1 deficient and therefore do not generate mature IL‐1β develop normally and the ex vivo response of cells to various apoptotic stimuli is indistinguishable from cells derived from wild‐type animals [12]. In addition, as 7β‐hydroxycholesterol and 7‐ketocholesterol can stimulate IL‐8 production which is chemotactic for T lymphocytes and neutrophils at picomolar and nanomolar concentrations [37], and as IL‐1 can induce both in vitro and in vivo endothelial expression of the adhesion molecules E‐selectin, ICAM‐1 and VCAM‐1 which are involved in the local adhesion and the subendothelial accumulation of T‐cells and monocytes [38, 39], we speculate that these oxysterols could play a critical role in the recruitment of immunocompetent cells in the atherosclerotic plaque. Interestingly, Bcl‐2 overexpression was associated with a lower IL‐1β secretion in U4 cells treated with 7β‐hydroxycholesterol than in U4 cells treated with 7‐ketocholesterol suggesting that the biological effects of oxysterols could be structure dependent as previously supposed by the various potencies of these compounds to induce apoptosis [3, 5]and to inhibit 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase activity [40].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the differentially expressed known genes, the cellular adhesion molecule ICAM-1 has been reported to be induced in in vitro stimulated human SMCs (25), in addition to its induction in endothelial cells. Moreover, ICAM-1 is expressed in neointimal SMCs in the atherosclerotic lesion (26,27). Induction of GM-CSF expression in cultured SMCs has been well documented (4,28), whereas expression in the atherosclerotic vessel wall has only been reported in rabbits (29).…”
Section: Isolation Of Full-length Cdnasmentioning
confidence: 99%
“…Normal intima of the aorta and femoral artery as well as atherosclerotic plaques contain SMC which similarly to embryonal SMC express cytokeratin-8 and ICAM-1 [8,10,15]. Previously, we showed that SMC lacking h-caldesmon and/or calponin are phenotypicaUy similar to embryonal SMC and are present in the intima of adult human aorta and in uncomplicated atherosclerotic plaques [2,5].…”
Section: Resultsmentioning
confidence: 99%